NSTP-CWTS of the Higher Education System: The Philippine Experience - Victoria, Edna Liza (JPAIR Institutional Research, 2017)
The NSTP-CWTS is an effective/good educational innovation in the tertiary education in the Philippines under the Republic Act No. 9163 known as the Act of Establishing the National Service Training Program (NSTP) for Tertiary Level Students. The study explored the HEIs ' contextualized practice on NSTP-CWTS course regarding the syllabi, community activities, and evaluation scheme. It utilized a mixed design of quantitative (survey) and qualitative (appreciative inquiry) methods. Twenty-two selected HEIs in Central Luzon represented by 22 faculty and 643 students were involved as the respondents. Using Stake's Responsive Model of evaluation, the triangulated data from survey questionnaire, interview, and focus group discussion revealed that the HEI respondents demonstrate great extent of contextualized CWTS practice under the CHED standards. Likewise, the quantitative and qualitative results indicate the unified practice on the functionality of syllabi, methodology, nature of community activities, and learning assessment criteria. The community activities were comprised largely of ecological-environmental initiatives like tree planting, lecture on climate change, proper solid waste management, and calamity-disaster preparedness. This paper proposed an indigenous framework "Kalingang Tugon sa Kapwa at Kalikasan" or "KaTUKK" for integration in the community service education of the HEIs in the Philippines and neighboring ASEAN countries.
Keywords: National service training program; civic welfare training service; community activities; mixed design